Caracterização morfologia de genótipos e formação de raízes em estacas caulinares de Pinheira (Annona squamosa L.) - Salvador, Taciana de Lima (2011)
Sugar apple (Annona squamosa L.), tropical fruit species, has brought attention of the new fruit markets around the world due to its exotic taste and attractive skin. In Brazilian orchards, genotypic differences among plants can be found arising from its alogamic sexual profile and the possibility of occuring natural mutations in the field. This study aimed primarily to establish a minimum list of morphologycal descriptors able to compare, separate and establish sugar apple cultivars. For this, we compared the typical cv. Crioula with the cv. Verdinha, a natural mutant that shows some differences to the standard Crioula type. Secondly, we studied a protocol for vegetative propagation by cuttings to clone the new established cultivar. For this, softwood cuttings of the cv. Verdinha treated with synthetic auxin (IBA) in the form of powder or liquid, at concentrations of 0, 1000, 2000, 3000 and 4000 mg/kg, associated to silver thiosulfate (STS) an known inhibitor of ethylene action at concentrations of 0, 2 and 4 mM. Finally, we studied the emergence of adventitious roots at the base of sugar apple cuttings, a considered difficult-to-root species. The results showed that it is possible to differentiate genotypes of sugar apple by using a list of simple morphological descriptors easily observed in branches, leaves and fruits. Cloning sugar apple by cuttings is a viable technique and it will possibly have commercial applications. Anatomical studies on adventitious roots formation in sugar apple leafy cuttings showed they arise indirectly from the healing callus tissues regardless of the use of IBA.